KEPEMIMPINAN OTENTIK: SEBUAH TINJAUAN - Ariyani, Desi (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
This article aims to conduct a review of research on authentic leadership. The review covers the dimensions, concepts, antecedents and benefits of authentic leadership. A review was carried out on 20 researchs results that were publish in international journals between 2008-2020. The results on the review showed that studies on leadership are increasingly focusing not only on the authenticity or genuineness of leaders but also the role of followers in them as an important part in providing legitimacy to authentic leadership. Discussion of the results of existing research reviews has implications for recommendations for further research.